The tumor microenvironment in hepatocellular carcinoma: mechanistic insights and therapeutic potential of traditional Chinese medicine - Xiaojun Su; Xiuli Yan; Hui Zhang (Molecular Cancer)
Abstract Hepatocellular carcinoma (HCC) progression and therapeutic resistance are profoundly influenced by the dynamic interplay within the tumor microenvironment (TME). The HCC TME comprises a complex network of cellular components, including cancer-associated fibroblasts, tumor-associated macrophages, and infiltrating immune cells, alongside non-cellular factors such as extracellular matrix proteins, cytokines, and angiogenic mediators. These elements collectively promote immune evasion, stromal remodeling, and neovascularization, driving tumor aggressiveness and treatment resistance. Emerging evidence suggests that traditional Chinese medicine (TCM) may offer a promising strategy to reprogram the immunosuppressive HCC TME through multimodal mechanisms, such as immunomodulation to enhance anti-tumor immunity and deplete regulatory cell populations, stromal normalization to attenuate fibroblast activation and pathological matrix deposition, and anti-angiogenic effects to restrict tumor vascularization. Notably, TCM compounds exhibit synergistic potential when combined with conventional therapies, including immune checkpoint inhibitors, tyrosine kinase inhibitors, and cytotoxic regimens, potentially enhancing efficacy while mitigating adverse effects. However, key challenges persist, such as intratumoral heterogeneity, pharmacokinetic variability of herbal formulations, and the need for rigorous preclinical-to-clinical translation. Future investigations should prioritize systems-level dissection of TCM-mediated TME modulation using omics technologies, rational design of TCM-based combination therapies guided by mechanistic studies, and standardization of clinically translatable TCM regimens. This review synthesizes current understanding of TME-driven HCC pathogenesis and highlights the emerging paradigm of TCM as a complementary modality to recalibrate the tumor-immune-stroma axis for improved therapeutic outcomes.